Infant’s Growth and Development at the Age of 6-12 Months Based on Breasfeeding - Maida Ayu Ara; Etty Sudaryati; Zulhaida Lubis (International Journal of Public Health Science (IJPHS), 2018)
Infancy is a golden and critical period in the cycle of life. In this period, an infant that is not provided with exclusive breastfeeding has 14 times higher risk to death compared with an infant that is provided with exclusive breastfeeding. Malnutrition in the first year causes reduced brain cells up to 15-20% which leads to impaired growth and development of infant. Exclusive breastfeeding can fulfill the need for nutrients within the first 6 months of life. The objective of this study was to analyze the difference in growth and development of infants at the age of 6-12 months based on breastfeeding in the working area of Puskesmas Perawatan Ngkeran, Aceh Tenggara Regency. This is used comparative analytical resaerch with cross sectional design. The sample was 124 infants consisting of 62 infants with exclusive breastfeeding and 62 non exclusive breastfeeding, taken by purposive sampling. The data were collected by using questionnaires through interviews, measurement and observation. They were analyzed using chi square and logistic regression testing for confounding check. The results showed that there was a significant difference in growth and development of infants based on breastfeeding (p value=0.000) with prevalence ratio (PR)=4.167 (95%CI: 1.867-9.301), which indicated that the infant who did not get exclusive breastfeeding had 4.167 times higher risk to experience bad growth and development. Based on the examination of confounding variable found that food supplementation was the variable with the risk that influences infant’s growth and development. Mothers are expected to practice exclusive breastfeeding, health practitioners are suggested to conduct more counseling of exclusive breastfeeding for pregnant mothers, to have early breastfeeding initiation, to create supporting groups of exclusive breastfeeding and to issue health policy of exclusive breastfeeding.